Carga microbiológica de las diferentes etapas del proceso de elaboración de queso fresco en la planta procesadora “CE-CE-PE” ubicada en el Cantón “Flavio Alfaro” de la Provincia de Manabí. - Avilés Álvarez, Omar Gregorio (2016)
The objective of this research was to evaluate the microbiological load of the different stages of the process of processing fresh cheese in the processing plant "CE-CE-PE" Located in the "Flavio Alfaro" Canton of the province of Manabí. The samples were: a) raw milk, pasteurized milk, curd and cheese at the end of the process in the plant (dispatch phase), b) service water taken at various points within the process area. C) materials used at the beginning of the process and at the end after cleaning (tubs, work table, molds, lira, shovels, canvas. This sampling will be done 2 times in the different stages of the process throughout the processing. Microbiological analyzes were performed according to INEN standards such as fecal coliforms, E. coli, molds, yeasts, salmonella and Staphylococcus aureos. It was evidenced that although pasteurisation proved to be efficient in the destruction of microorganisms and the use of salt in the cheeses destroy most of the microorganisms present in the curd, in the process of manufacture of the cheese there are deficient practices of manufacture as in the Procedures of hygiene of the materials and operators, therefore the Plant must adopt the corrective measures corresponding to the deficiencies found.